Results without authority : controlling a project when the team doesn't report to you - Kendrick, Tom (AMACOM, 2006)
"This book delivers proven techniques for controlling projects and managing diverse teams in a wide variety of situations, and bringing those projects to successful closure. The concepts in this book are essential for all project managers, with and without authority, because they offer a productive alternative to "command and control" management techniques that can easily backfire."--Jacket.